2017
DOI: 10.1002/jat.3553
|View full text |Cite
|
Sign up to set email alerts
|

A toxicogenomics approach to screen chlorinated flame retardants tris(2‐chloroethyl) phosphate and tris(2‐chloroisopropyl) phosphate for potential health effects

Abstract: Tris(2-chloroethyl) phosphate (TCEP) is a pervasive flame retardant that has been identified as a chemical of concern given its health effects and therefore its use has since been tightly regulated. Tris(2-chloroisopropyl) phosphate (TCIPP), an analogue of TCEP, is believed to be its replacement. However, compared to TCEP, little is known of the toxicological impacts of TCIPP. We used RNA sequencing as unbiased and sensitive tool to identify and compare effects on a transcriptome level of TCEP and TCIPP in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(9 citation statements)
references
References 71 publications
0
8
0
Order By: Relevance
“…Evidence from in vitro studies suggest that exposure to >50 μM OPEs, including TPhP and TDCiPP, can modulate oxidative stress biomarkers and are immunotoxic for dendritic cells from mice, which elicit immune responses to pathogens in the airway . Similarly, human exposure studies have demonstrated that urinary metabolites of TCEP, TnBP, and TPhP among adults and urinary metabolites of TBOEP, TPhP, and EHDPP among children have been associated with higher levels of oxidative stress biomarkers such as 4-hydroxynonenal (HNE), hexanoyl-lysine (HEL), and 8-hydroxy-2′-deoxyguanosine (8-OHdG). , Toxicogenomic studies have also demonstrated that OPEs, such as TBOEP, can alter genes involved in immune response. , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence from in vitro studies suggest that exposure to >50 μM OPEs, including TPhP and TDCiPP, can modulate oxidative stress biomarkers and are immunotoxic for dendritic cells from mice, which elicit immune responses to pathogens in the airway . Similarly, human exposure studies have demonstrated that urinary metabolites of TCEP, TnBP, and TPhP among adults and urinary metabolites of TBOEP, TPhP, and EHDPP among children have been associated with higher levels of oxidative stress biomarkers such as 4-hydroxynonenal (HNE), hexanoyl-lysine (HEL), and 8-hydroxy-2′-deoxyguanosine (8-OHdG). , Toxicogenomic studies have also demonstrated that OPEs, such as TBOEP, can alter genes involved in immune response. , …”
Section: Resultsmentioning
confidence: 99%
“…54,55 Toxicogenomic studies have also demonstrated that OPEs, such as TBOEP, can alter genes involved in immune response. 56,57 Implications. This study examined early life exposure to a wide range of OPEs and their association with childhood asthma diagnosed at age 5.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Human hepatocellular (HepG2) cells exposed to a combined mixture of TCEP and benzo (a) pyrene demonstrated the release of inflammatory responses (IL-6 and IL-8) via activation of the EGFR-ERK1/2 pathway [18]. RNA sequencing (RNA-Seq) of HepG2 cells exposed to TCEP at sublethal concentrations affected several genes related to xenobiotic metabolism, immune responses, and steroid hormone biosynthesis [19]. Furthermore, HepG2 cells exposed to TCEP demonstrated cytotoxicity and growth arrest through attenuation of the SIRT1-independent PI3K/Akt/mTOR pathway [20].…”
Section: Introductionmentioning
confidence: 99%
“…Canbaz et al (Canbaz, Logiantara, van Ree, & van Rijt, 2017) revealed that TDCIPP and triphenyl phosphate may promote DC activation and proinflammatory cytokine production in vitro. Krivoshiev et al reported that TBEP, tris(2‐chloroethyl) phosphate, and TCIPP had a significant impact on the expression of immune response genes and steroid hormone biosynthesis‐related genes in HepG2 cells (Krivoshiev, Beemster, Sprangers, Blust, & Husson, 2018; Krivoshiev, Beemster, Sprangers, Cuypers, et al, 2018). An epidemiological study revealed a strong positive association between TBEP metabolites in urine and eczema (Araki et al, 2018).…”
Section: Discussionmentioning
confidence: 99%